Information technology and competitive advantage : lessons from developed countries. - CANE, Alan (1992)
Presents a history of IT and discusses the main elements of an IT infrastructure. Discusses strategies for using IT, emphasizing that IT is only one instrument for enhancing competitiveness. Considers the implications for developing countries, including strategies for technology transfer.